Decreased Left Putamen and Thalamus Volume Correlates with Delusions in First-Episode Schizophrenia Patients - Huang, Xiaojun; Pu, Weidan; Li, Xinmin; Greenshaw, Andrew J.; Dursun, Serdar M.; Xue, Zhimin; Liu, Haihong; Liu, Zhening (Frontiers in Psychiatry, 2017)
Abstract Background: Delusional thinking is one of the hallmark symptoms of schizophrenia. However, the underlying neural substrate for delusions in schizophrenia remains unknown. In an attempt to further our understanding of the neural basis of delusions, we explored gray matter deficits and their clinical associations in first-episode schizophrenia patients with and without delusions. Methods: Twenty-four first-episode schizophrenia patients with delusions and 18 without delusions as well as 26 healthy controls underwent clinical assessment and whole brain structural imaging which were acquired a 3.0T scanner. Voxel-based morphometry was used to explore inter-group differences in gray matter volume using analysis of covariance, and Spearman correlation coefficients (rho) between the Scale for the Assessment of Positive Symptoms (SAPS)-delusion scores and mean regional brain volumes was obtained. Results: Patients with delusions showed decreased brain gray matter volumes in the left putamen, thalamus and caudate regions compared to healthy controls. Patients with delusions also showed decreased regional volume in the left putamen and thalamus compared to patients without delusions. SAPS-delusion scores were negatively correlated with the gray matter volumes of the left putamen and thalamus. Discussion: Left putamen and thalamus volume loss may be biological correlates of delusions in schizophrenia.